Pendekatan Fault Tree Analysis Untuk Pelaksanaan K3 pada PT. Kunango Jantan Padang - Yusrizal Bakar (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
This research is intended to see how far efforts to prevent the risk of work accidents and work-related diseases can be minimized by carrying out other constructive efforts, the implementation of Occupational Safety and Health will not run well if the involvement of all parties is not optimal according to their roles and functions. Besides that, this research is also aimed at knowing the Occupational Health and Safety management system, the dangers of work accidents and the factors that cause work accidents that occur in companies. The method used is the Fault Tree Analysis (FTA) approach involving employees based on the Hazard Identification Risk Assessment (HIRA) and SWOT analysis. The results of the study show that in the HIRA method, there are 3 types of production activities that have a high enough risk rating number (RRN). The main cause of work accidents with the FTA method is the potential for work accidents to occur, namely the finger caught in the mold head and pain in the back. For the SWOT matrix, the methods used by the company to achieve good growth include involving employees through efforts to create an Occupational Safety and Health team to monitor and evaluate the implementation of the Occupational Safety and Health program, create an administrative system that aims to manage the Safety management system and Occupational Health, as well as socialization regarding Occupational Safety and Health. By empowering employees in Occupational Health and Safety management, it is hoped that zero incidents will be achieved later.